Developing Airport Vocabulary Learning Materials for Air Transport Management Students - Herida Panji Olivia Azhar (Journal of Nusantara Education, 2022)
Vocabulary mastery is an important component in language learning. In English language teaching, some vocabulary learning materials are developed based on themes for example, English vocabulary for business, economics, law and medicine. In aviation, most vocabulary books focus on vocabulary for pilots, Air Traffic Controllers, Mechanics, and Flight Attendants. In fact, these are not the only professions in the field. With this in mind, this study aims to develop airport vocabulary learning materials. This study used research and development design. The process of the material development involved planning, designing, and development. Then, the vocabulary learning material was validated through a questionnaire. The respondents were six English Lecturers and 10 people who work at the airport at the managerial levels. The results were analyzed using descriptive statistics. The validity and reliability of the instrument were tested using Pearson correlation and Cronbach alpha respectively. The result of the material development is the airport vocabulary learning materials. The content includes the names of places at the airport, tools and equipment, facilities, and the activities at the airport. The results of the questionnaire analysis show high mean score for the learning and teaching aspect and the general attribute of the materials. The implication of this study is that the vocabulary learning materials can be used as supplementary materials for Air transport Management students. In addition to that, the instructors may use the materials to support the teaching and learning process in the English for Airport Management course. Further studies can be conducted on the students’ attitude and views on the use of the vocabulary learning materials. Penguasaan kosakata merupakan salah satu komponen penting dalam pembelajaran bahasa Inggris. Materi pembelajaran ini biasanya dikembangkan berdasarkan tema tertentu seperti English vocabulary for business, English vocabulary for economics, English vocabulary for law and English vocabulary for medicine. Dalam penerbangan, sebagian besar buku English vocabulary berfokus pada kosakata untuk Pilot, Petugas Air Traffic Controller, Mekanik, dan Awak Kabin. Padahal, profesi ini bukan satu-satunya pekerjaan di dunia penerbangan. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengembangkan materi pembelajaran kosakata dengan tema kebandarudaraan. Penelitian ini menggunakan desain penelitian dan pengembangan. Proses pengembangan materi meliputi perencanaan, desain dan pengembangan. Kemudian hasil pengembangan divalidasi melalui angket dan disebarkan kepada 16 orang responden yang dipilih secara purposif. Responden terdiri dari 6 dosen bahasa Inggris dan 10 orang praktisi kebandarudaraan. Hasil dari angket kemudian dianalisis menggunakan statistik deskriptif. Validitas dan reliabilitas instrumen diuji  menggunakan Pearson-product moment dan alpha Cronbach. Pengembangan menghasilkan produk berupa vocabulary learning materials yang disusun berdasarkan tema seperti nama-nama tempat di Bandar Udara, alat dan perlengkapan, fasilitas, dan kegiatan di Bandar Udara. Hasil analisis angket menunjukkan nilai rata-rata yang tinggi untuk aspek belajar mengajar dan atribut umum materi. Implikasi dari penelitian ini adalah materi pembelajaran kosa kata dapat dijadikan sebagai materi pelengkap bagi mahasiswa Manajemen Transportasi Udara. Selain itu, instruktur dapat menggunakan materi untuk mendukung proses belajar mengajar dalam pembelajaran Bahasa Inggris untuk Manajemen Bandara. Studi lebih lanjut dapat dilakukan pada sikap dan pandangan mahasiswa tentang penggunaan materi pembelajaran ini.